2005
DOI: 10.1007/s10740-005-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of a vapor film on a highly superheated surface immersed in subcooled water

Abstract: Results are given of an experimental investigation of the behavior of a vapor film on a highly superheated hemispherical surface immersed in water subcooled to the saturation temperature. The conditions of existence of vapor films on a hot surface and the characteristics of their collapse from the heating surface and transition to nucleate boiling are revealed, as well as the effects which accompany the vanishing of vapor film. The possibilities of internal triggering of fine fragmentation of hot melt and vapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Modeling representations of the boiling of the subcooled water under forced flow have been studied and also a comprehensive analysis has been conducted [18][19][20][21][22][23][24]. It is found that at subcooling temperatures over 50 • the hydraulic resistance coefficients equal under the boiling and forced convection of a single-phase liquid at non-isothermal flow.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…Modeling representations of the boiling of the subcooled water under forced flow have been studied and also a comprehensive analysis has been conducted [18][19][20][21][22][23][24]. It is found that at subcooling temperatures over 50 • the hydraulic resistance coefficients equal under the boiling and forced convection of a single-phase liquid at non-isothermal flow.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%